PENGARUH TERAPI RENDAM KAKI MENGGUNAKAN AIR HANGATUNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN HIPERTENSI DIPUSKESMAS KOTA DATAR - Shakira Hadisti Rosidi; Muhammad Taufik Daniel Hasibuan (Jurnal Riset Multidisiplin Edukasi, 2025)
Hypertension is a non-communicable disease which is one of the main causes of death in the world and is a risk that leads to complications such as heart attacks, strokes, diabetes and kidney disease. This study aims to determine the effect of foot soak therapy using warm water to reduce blood pressure in hypertensive patients at the Kota Datar Community Health Center. The population in this study was 519 people. This research uses a quasi-experiment method with a pre-test, post-test with control group design. The research sampling method used a purposive sampling technique with a research sample of 40 people divided into 2 groups, each group divided into 20 people. The intervention group was given a warm water foot soak for 15 minutes for 7 consecutive days, while the control group was not given a warm water foot soak. The results of the study using an independent t-test which tested the control group and intervention group showed that the p value was 0.033 (<0.05), so it can be concluded that there is an effect of soaking feet using warm water on hypertensive patients. It is recommended to conduct further research with a larger sample and add other variables such as cold water foot soak therapy.